Simulation and Analysis of Pressure Waves in Flow Channels of Axial and Radial Gas Wave Ejectors - Haoran, Li; Yiming, Zhao; Dapeng, Hu (Recent Patents on Engineering, 2025)
IntroductionAs an efficient energy transfer technology, the gas wave ejector (GWE) holds several patents poised to address the challenges of low-carbon energy. These patents find applications in numerous fields. Traditional axial-flow GWE patents encounter limitations under certain application conditions, whereas radial-flow GWE patents offer an effective solution to these issues. However, the mechanisms behind the performance differences between these two types of GWEs have not yet been studied.ObjectiveSince pressure waves are central to energy transfer in wave rotors, this study analyzes the coupling effects of centrifugal forces and pressure waves. By examining the differences in pressure wave intensity and propagation velocity within two types of wave rotor channels, the mechanisms underlying the performance disparities are elucidated.MethodsFluent was utilized for numerical simulations, and Response Surface Methodology was employed to model the influence of various factors.Results and DiscussionIt can be observed that the propagation velocity and intensity of pressure waves changed under the influence of centrifugal forces. The propagation velocities of S1 and E2, which propagate in the same direction as the fluid flow within the rotor, increase 9% and 32% respectively, whereas the propagation speed of E1, which propagates in the opposite direction of the fluid flow, decreases 15%. Regarding the intensity of each pressure wave, the coupling effect of centrifugal force resulted in an increase of 1.04 to 2.55 kPa. This paper is the first to fit a relational expression for the speed differential of pressure wave propagation within axial and radial flow channels, correlating the main pressure wave velocities (S1, E1, E2) with flow channel length, rotational speed, compression ratio, and expansion ratio, thus providing a reference for GWE design and analysis. Through analysis of variance and significance tests, it is evident that each parameter significantly contributes to the fitting degree of the pressure wave propagation velocity difference (p < 0.01). Furthermore, the inadequacy test (F-value=2.36 3.56) suggests a low level of discrepancy.ConclusionThe fundamental reason for the performance disparity between the two types of gas wave ejectors (GWE) lies in the discrepancies in pressure wave intensity and propagation velocity resulting from centrifugal force effects. Based on the fitted relationships, theoretical foundations can be provided for subsequent wave rotor design and performance analysis. For example, the differences in pressure wave propagation speed can inform the design and analysis of corresponding pressure ports.
Keywords: numerical simulation